2017
DOI: 10.1186/s12887-017-0881-1
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pneumonia pattern on day 7 chest radiograph predicts bronchopulmonary dysplasia in preterm infants

Abstract: BackgroundEarly identification of infants at higher risk of developing bronchopulmonary dysplasia (BPD) may enable a targeted approach to reduce BPD. We aimed to evaluate the hypothesis that the interstitial pneumonia pattern on the day 7 chest radiograph predicts BPD or death before 36 weeks postmenstrual age (PMA).MethodsA retrospective cohort study was performed on 336 preterm infants (birth weight < 1500 g and gestational age < 32 postmenstrual weeks) who were admitted to a single tertiary academic center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
(44 reference statements)
0
23
0
Order By: Relevance
“…Using thoracic X‐ray, Kim et al reported that the existence of an interstitial infiltrate at 7 DOL predicts the later development of BPD in VLBWI . This interstitial infiltrate in the thoracic X‐ray correlates well with the existence of multiple B‐lines in LU .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using thoracic X‐ray, Kim et al reported that the existence of an interstitial infiltrate at 7 DOL predicts the later development of BPD in VLBWI . This interstitial infiltrate in the thoracic X‐ray correlates well with the existence of multiple B‐lines in LU .…”
Section: Discussionmentioning
confidence: 99%
“…Detecting early signs of this lung disease is challenging, and in the absence of a reliable marker for this evolving disorder, a window of opportunity to provide specific treatment or further adapt respiratory support is often missed. Cytokines and various proteins in blood or tracheal aspirate, as well as thoracic X‐rays have been studied as potential biomarkers for BPD, but none has been proven sufficiently robust to be utilized in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the chest radiograph classification did not have a scoring system. It has also been reported that the simple scoring or appearance of chest radiograph on postnatal day 7 predicts BPD36 . BPD36 was predicted using a simple BPD scoring systems resembling the present chest radiograph classification, using terms such as emphysematous/fibrous or hazy appearance .…”
Section: Discussionmentioning
confidence: 64%
“…It has also been reported that the simple scoring or appearance of chest radiograph on postnatal day 7 predicts BPD36. 12,13 BPD36 was predicted using a simple BPD scoring systems resembling the present chest radiograph classification, using terms such as emphysematous/fibrous or hazy appearance. 12,13 Therefore, further studies to identify simple scoring systems correlated with bubbly/cystic appearance on chest radiograph are required to validate the present chest radiograph classification.…”
Section: Discussionmentioning
confidence: 99%